Norm of an integral-type operator from Dirichlet to Bloch space on the unit disk - Stević, Stevo, (Utilitas Mathematica, 2010)
This short note calculates the operator norm of an integral-type operator from the Dirichlet space to the Bloch-type space on the unit disk.